2022
DOI: 10.33265/polar.v41.7884
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of the wind field around Ny-Ålesund, Svalbard, using unmanned aircraft

Abstract: The wind field in Arctic fjords is strongly influenced by glaciers, local orography and the interaction between sea and land. Ny-Ålesund, an important location for atmospheric research in the Arctic, is located in Kongsfjorden, a fjord with a complex local wind field that influences measurements in Ny-Ålesund. Using wind measurements from UAS (unmanned aircraft systems), ground measurements, radiosonde and reanalysis data, characteristic processes that determine the wind field around Ny-Ålesund are identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The fjord is oriented northwestsoutheast and is surrounded by plateaus and mountains of about 500-1000 m altitude. Their presence affects the local wind circulation and the advection of air masses (Maturilli and Kayser, 2017;Gierens et al, 2020;Schön et al, 2022).…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…The fjord is oriented northwestsoutheast and is surrounded by plateaus and mountains of about 500-1000 m altitude. Their presence affects the local wind circulation and the advection of air masses (Maturilli and Kayser, 2017;Gierens et al, 2020;Schön et al, 2022).…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…During summer, there is also a frequent north-west to south-west wind, caused by drainage flows from the Zeppelin Mountain to the fjord and low wind speed from the open sea (e.g., Beine et al, 2001;Mazzola et al, 2016). However, the wind regimes are mainly valid for the lowermost 500 m (Graßl et al, 2022), like measured at Old Pier or at the Gruvebadet observatory that is also influenced by a katabatic flow from the Broggerbreen in the west (Schön et al, 2022a). The latter is situated southwest of the village of Ny-Ålesund and south-east of the airfield at a respective distance of around 1 km (see Fig.…”
mentioning
confidence: 98%
“…Processes above land in comparison with processes above open water or sea ice can be investigated by UAS operations as low altitudes. In this article, the focus is on the results of aerosol observations rather than on the technical background of the campaign that was already introduced in , and a general review of UAS campaigns in Svalbard is not in the scope of this publication and other case studies of the ALADINA period have already been subject to publications shown in , Petäjä et al (2020), Schön et al (2022a) and Xavier et al (2022).…”
mentioning
confidence: 99%